Genome and transcriptome-wide study of carbamoyltransferase genes in major fleshy fruits: A multi-omics study of evolution and functional significance - Dhar, Yogeshwar V.; Asif, Mehar H. (Frontiers in Plant Science, 2022)
The carbamoyltransferase or ATCase/OTCase, is an evolutionary related conserved protein family, which contains 2 genes, aspartate carbamoyltransferase (ATCase) and ornithine carbamoyltransferase (OTCase).Where, ATCase; which is textbook example of the allosteric regulation, plays a pivotal role in pyrimidine biosynthesis, with its unique protein structure which includes sectional catalytic and regulatory subunits, the second member OTCase, catalytically regulates the conversion of ornithine to citrulline.. Although they are identified in some plants, yet no complete genomics study is available, emphasizing their role in fruit ripening. In present study, the 393 carbamoyltransferase genes were identified in plant kingdom along with 30 fleshy fruit representatives. Their detailed phylogeny, evolutionary patterns with their expression during the process of fruit ripening was analysed. To understand the impact of methylation, the methylation status of carbamoyltransferase genes was also analysed in the study. The present study aims to provide the detailed study of carbamoyltransferase genes in fleshy fruit bearing plants and investigates their expression based functional genomic profile with phylogenomic evolutionary signatures, to understand their involvement in fruit ripening mechanism.